Phosphorus fractions and their relationships with soil chemical attributes in an integrated crop-livestock system under annual phosphates fertilization - Guera, Keli Cristina Silva; da Fonseca, Adriel Ferreira (Frontiers in Sustainable Food Systems, 2022)
The main factors affecting phosphorus (P) availability in soils are mineralogy, acidity, and concentration of elements in the soil solution. Moreover, P fertilizer sources and amounts can affect P cycling and adsorption of this element on colloids. In this research, we hypothesized that the use of phosphate sources of different solubilities can alter soil P adsorption process, due to chemical compositions of these sources and, in ICLS, the soil-plant-animal system can change the P forms distribution on soil profile and its interactions with the soil chemical attributes. To examine these hypotheses, a field experiment was conducted over five years, under a Haplic Cambisol, in an incomplete factorial scheme, with the treatments being composed of three P sources (triple superphosphate, rock phosphate - Arad and magnesium thermophosphate), three doses of total P2O5 (60, 120 and 180 kg ha-1) plus a treatment without application of phosphate fertilizer. Phosphate applications occurred annually, broadcast without incorporation, at the time of sowing the annual winter forage, in a crop rotation system that included pasture in autumn-winter and grain crops in spring-summer. Soil samples were collected at depths of 0 to 5, 5 to 10, 10 to 15, 15 to 20 and 20 to 30 cm and evaluated by Hedley P fractionation and the soil chemical attributes were quantified. The use of different phosphates applied broadcast without incorporation did not influence the concentrations of soil P fractions over a five-year study. Phosphate fertilizer doses above 120 kg ha-1 of total P2O5 increased moderately labile and non-labile P fractions. The highest concentration of labile P was found up to 15 cm soil depth. It was found that P lability is strongly associated with calcium and total organic carbon concentrations in the soil profile. High concentrations of basic cations and sulfate in the soil solution increased moderately labile and non-labile P fractions. The complexity of ICLS interactions to maintain phosphorus dynamics in the soil was shown to be an intricate P release/adsorption process associated with soil chemical attributes.